Latihan Hadroh di Dusun Banyunganti Kidul (Studi Living Hadis : Teori Fungsional Thomas F. O’dea) - Reza Bakhtiar Ramadhan (Jurnal Living Hadis, 2017)
Hadith about fadhilah (virtue) of reading shalawat has penetrated the soul of society in Banyunganti Kidul. Hadroh and shalawat exercise get more popular at Banyunganti Kidul, so it’s always held on every week. This social phenomenon implies that religion becomes one of the important indicators. Especially the hadiths relating to command and fadhilah (virtue) give shalawat on prophets. Thus forming the mindset and religious spirit of Banyunganti Kidul’s society.This phenomenon is also called by living hadith. The phenomenology approach especially functional theory became the focus of this study. It can be concluded that this phenomenon is a growing tradition in society. It is also a study of contemporary hadith that can shift the existence of previous hadith research.